Nostalgia as a Resource for Psychological Health and Well‐Being. Issue 11 (4th November 2013) - Routledge, Clay; Wildschut, Tim; Sedikides, Constantine; Juhl, Jacob
Abstract: Historically, nostalgia has been viewed as a disease of the brain or the mind. However, in recent years, nostalgia has received a conceptual rehabilitation due to a revival of scholarly interest accompanied by the use of contemporary empirical methods. Drawing upon this recent work, we propose that nostalgia is an important resource for psychological health and well‐being. We begin by detailing the characteristics of the nostalgic experience and then discuss a wide range of studies demonstrating that psychological threat triggers nostalgia, nostalgia enhances psychological health and well‐being, and nostalgia promotes adaptive psychological functioning among individuals at risk for poor mental health. We also highlight the need for future research on nostalgia's relation to psychological health.